THE EXLPOITATION OF THE MICROTEACHING PRACTICE IN SHAPING ELT PRE-SERVICE TEACHERS’ SELF-EFFICACY = KHAI THÁC HOẠT ĐỘNG GIẢNG TẬP (MICROTEACHING PRACTICE) NHẰM PHÁT TRIỂN HIỆU LỰC BẢN THÂN CỦA SINH VIÊN SƯ PHẠM TIẾNG ANH - Trần, Thị Hoài Linh (2020)
Microteaching practice have been incorporated in courses of ESL/EFL classroom techniques and practices and Lesson planning and material development at the Faculty of English Language Teacher Education, University of Languages and International Studies, playing the role of intersection between theory and practice of pedagogical skills. This study aimed at examining the exploitation of the microteaching practice in such courses in shaping ELT pre-service teachers self-efficacy, as perceived by the student teachers. The data of the research were collected via two main gathering tools which are survey questionnaire and semi-structured interviews. Specifically, after being collected, 121 surveys were analyzed and set the foundation for the conduct of personal interviews between the researcher and five pre-service teachers. Afterwards, the content analysis was utilized to process the qualitative data.